The world of urban sketching : celebrating the evolution of drawing & painting on location around the globe : new inspirations to see your world one sketch at a time /: celebrating the evolution of drawing & painting on location around the globe : new inspirations to see your world one sketch at a time. (2022) - Bower, Stephanie
No abstract available